IMPROVING THE QUALITY OF PROSTATE TRANSURETHRAL RESECTION IN PATIENTS WITH BENIGN PROSTATIC HYPERPLASIA THROUGH INTRAOPERATIVE TRANSRECTAL ULTRASOUND MONITORING OF THE REMOVED TISSUE VOLUME - V. B. Filimonov; R. V. Vasin; I. S. Sobennikov (Исследования и практика в медицине)
Purpose of the study. To improve the quality of prostate transurethral resection by means of intraoperative ultrasound monitoring of the removed tissue volume.Patients and methods. The study included 92 patients who, according to indications, underwent prostate transurethral resection. Patients were divided into 2 groups. The 1st group included patients (n = 50) operated on using the method of monitoring the removed tissue volume, proposed in the study. The average age of patients in this group was 67.4 ± 3.88 years, the average prostate volume before surgery was 59.5 ± 4.5 cm3 with a range of values from 42 cm3 to 94 cm3. The 2nd group (n = 42) included patients operated on according to the classical method of prostate transurethral resection. The average age of patients in this group was 68.1 ± 2.9 years, the average prostate volume before surgery was 53.5 ± 4.5 cm3. Results. The average prostate volume atier surgery in patients of the 1st group was 23.2 ± 1.8 cm3. Thus, the average volume of the removed tissue was 63.2% of the prostate gland initial volume. The average prostate volume atier surgery in patients of the 2nd group was 25.6 ± 1.9 cm3 (p < 0.05). The average volume of the removed tissue was 52.1% of the prostate gland initial volume. The number of complications is comparable in groups of patients. When using the removed tissue control during surgery, it was possible to increase the resection radicality, which is reﬂ ected by a smaller average residual volume of the prostate gland (by 9.4%) atier surgery.Conclusion. The use of ultrasonic control of the prostate adenoma removed tissue volume during prostate transurethral resection does not increase the risks of possible postoperative complications, wherein increases radicality of the performed operation.